Digital Literacy and Its Implications for the Development of 21st Century Competencies - Mochammmad Syafiuddin Shobirin (International Journal of Islamic Pedagogical Research, 2025)
The rapid advancement of digital technology has brought significant changes to the educational landscape, requiring learners to possess competencies relevant to the demands of the 21st century. However, the level of digital literacy among learners is still uneven, and its role in supporting the development of 21st-century competencies has not been optimally understood. This study aims to analyze digital literacy and its implications for the development of 21st-century competencies in the context of education. The research employs a library research method by systematically reviewing and analyzing relevant scholarly literature, including books, national and international journal articles, and educational policy documents related to digital literacy and 21st-century skills. The data were analyzed using content analysis to identify key concepts, patterns, and relationships between digital literacy and 21st-century competencies. The findings indicate that digital literacy is a multidimensional competence encompassing technical, cognitive, critical, and ethical aspects, which plays a crucial role in fostering critical thinking, creativity, communication, and collaboration skills. Furthermore, digital literacy supports learner-centered learning, self-regulated learning, and lifelong learning. The implications of this study suggest that digital literacy should be positioned as a core competence within educational curricula and supported through comprehensive policies, teacher professional development, and conducive learning environments. Strengthening digital literacy is essential to enhance the quality